Trnp1 organizes diverse nuclear membrane-less compartments in neural stem cells. - Esgleas, Miriam; Falk, Sven; Forne, Ignasi; Thiry, Marc; Najas, Sonia; Zhang, Sirui; Mas-Sanchez, Aina; Geerlof, Arie; Niessing, Dierk; Wang, Zefeng; Imhof, Axel; Goetz, Magdalena (EMBO Journal, 2020)
TMF1-regulated nuclear protein 1 (Trnp1) has been shown to exert potent roles in neural development affecting neural stem cell self-renewal and brain folding, but its molecular function in the nucleus is still unknown. Here, we show that Trnp1 is a low complexity protein with the capacity to phase separate. Trnp1 interacts with factors located in several nuclear membrane-less organelles, the nucleolus, nuclear speckles, and condensed chromatin. Importantly, Trnp1 co-regulates the architecture and function of these nuclear compartments in vitro and in the developing brain in vivo. Deletion of a highly conserved region in the N-terminal intrinsic disordered region abolishes the capacity of Trnp1 to regulate nucleoli and heterochromatin size, proliferation, and M-phase length; decreases the capacity to phase separate; and abrogates most of Trnp1 protein interactions. Thus, we identified Trnp1 as a novel regulator of several nuclear membrane-less compartments, a function important to maintain cells in a self-renewing proliferative state.
EVALuna2:416067